If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = -6 + x Solving 4 = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + -1x = -6 + x + -1x Combine like terms: x + -1x = 0 4 + -1x = -6 + 0 4 + -1x = -6 Add '-4' to each side of the equation. 4 + -4 + -1x = -6 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = -6 + -4 -1x = -6 + -4 Combine like terms: -6 + -4 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10
| A+C=A | | 6+9=3x | | -30=3r | | 38=7b+10 | | 2(x-1)=10(1-x)+6 | | 3xy+4xy-xy= | | 4x+29=5-8(x+6) | | 25x^2-36=o | | 6(5y-1)=-2y-38 | | 2+4r=5+4r | | X*7-4x=19-2x | | 90=-6(1+8q) | | 1-5m+3m=3 | | -x^3-6x^2+36x+216=0 | | -8-3(w+13)=4(w+11)-7w | | 15=5/6c | | -2(3x+1)-6x+7= | | 3x-2=55 | | 3/4(x-1)=7/4 | | (1-k)X^2-2(1+k)X+3(k+1)=0 | | 3[5x-2]+27=-24 | | 2v^2+11v-5=0 | | C=5/9(50-32) | | 8a-2=3a+5.5 | | 6x-8x+2x= | | 4x+x+(4x+6)+(4x+6)2=166 | | j/2+7=12 | | 200=16x-(3) | | x^2+3*x=97 | | 3/(2r-3)=.6 | | x^2+3x=97 | | 75=9x(7) |